Association between general anesthesia and contrast-induced encephalopathy after endovascular treatment on neurovascular diseases - Zhong, Zhihong; Ni, Hongyang; Zhu, Jun; Jiang, Hong; Hu, Jinqing; Lin, Dong; Bian, Liuguan (Frontiers in Neurology, 2023)
Objective: Contrast-induced encephalopathy (CIE) is a rare neurological complication which can occur in the context of various endovascular procedures. Although many potential risk factors for CIE have been reported, it is still unclear whether anesthesia is a risk factor for the occurrence of CIE. The goal of this study was to investigate the incidence of CIE in patients who underwent endovascular treatment under different anesthesia methods and anesthetics administration, and explored whether general anesthesia was the potential risk factor of CIE. Methods: We retrospectively reviewed available clinical data from 1043 patients with neurovascular diseases undergoing endovascular treatment between June 2018 and June 2021 in our hospital. A propensity-score based matching strategy and logistic regression were used to analyze the association between anesthesia and the occurrence of CIE. Results: In this study, we implemented embolization of intracranial aneurysm in 412 patients, stent implantation of extracranial artery stenosis in 346, stent implantation of intracranial artery stenosis in 187, embolization of cerebral arteriovenous malformation or dural arteriovenous fistula in 54, endovascular thrombectomy in 20, and other endovascular treatments in 24. 370 patients (35.5%) received treatment under local anesthesia while the remaining 673 (64.5%) underwent treatment under general anesthesia. 14 patients were identified as CIE, resulting in a total incidence rate of 1.34%. After propensity-score based matching of anesthesia methods, the occurrence of CIE was significantly different between the general anesthesia and local anesthesia group (P=0.007). And after propensity-score based matching of CIE, the anesthesia methods were significantly different between the two groups. Pearson contingency coefficients and logistic regression showed significant correlation between general anesthesia and the risk of CIE. Conclusions: General anesthesia might be a risk factor of CIE, and propofol might be associated with the increased occurrence of CIE.